Dignity at work - Hodson, Randy (Cambridge University Press, 2001)
"Human dignity, the ability to establish a sense of self-worth and self-respect and to enjoy the respect of others, is necessary for a fully realized life. Working with dignity is a fundamental part of achieving a life well-lived, yet the workplace often poses challenging obstacles because of mismanagement or managerial abuse. Defending dignity and realizing self-respect through work are key to workers' well-being. Insuring the dignity of employees is equally important for organizations as they attempt to make effective use of their human capital. In this book Randy Hodson, a sociologist of work and organizational behavior, applies ethnographic and statistical approaches to this topic, offering both a richly detailed, inside look at real examples of dignity in action, and a broader analysis of the pivotal role of dignity at work. How do people attain and maintain dignity in the face of assaults on dignity at work? How can management within organizations help to preserve dignity and thus enhance workers' social relations, organizational integrity, and productivity? This book sheds valuable light on the mechanisms by which workers become satisfied and committed employees. Hodson's exploration of these questions includes ethnographic detail from diverse settings, ranging from automobile manufacturing, to medicine, to home-based sales and temporary clerical work. He focuses on four problems that deflate morale and create conflict: outright mismanagement and abuse, overwork, limits on autonomy, and contradictions of employee involvement. He also analyzes strategies that workers use to maintain and defend their dignity: resistance, citizenship, the creation of independent meaning systems, and the development of social relations at work. Hodson offers a valuable picture of the causes, consequences, and patterns of workers' efforts to maintain dignity. He finds that even in workplaces where abuse is common and mismanagement makes pride in accomplishment difficult, workers still find ways to create meaning in work and to achieve self-respect. He uses his findings and analysis to reevaluate contemporary workplace theories, including those based on the traditions of Marx, Weber, Durkheim, Foucault, and feminist theories of the workplace. Hodson's conceptual model of human agency and dignity contributes broadly to our understanding of the nature of work in advanced societies."--Publisher's description